2012
DOI: 10.1107/s0021889812007662
|View full text |Cite
|
Sign up to set email alerts
|

New developments in theATSASprogram package for small-angle scattering data analysis

Abstract: The paper presents new developments and amendments to the ATSAS package (version 2.4) for processing and analysis of isotropic small-angle scattering data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
1,888
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,646 publications
(1,951 citation statements)
references
References 48 publications
23
1,888
0
13
Order By: Relevance
“…The scattering curves were analysed using the programs Scatter and the package ATSAS to obtain the radius of gyration ( R g ), the maximum particle dimension ( D max ), the excluded particle volume ( V p ), the cross‐sectional radius and the pair distribution function (P(r)) (Petoukhov et al , 2012). The molecular mass of the scattering particles was estimated using a method described by Rambo (Rambo & Tainer, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The scattering curves were analysed using the programs Scatter and the package ATSAS to obtain the radius of gyration ( R g ), the maximum particle dimension ( D max ), the excluded particle volume ( V p ), the cross‐sectional radius and the pair distribution function (P(r)) (Petoukhov et al , 2012). The molecular mass of the scattering particles was estimated using a method described by Rambo (Rambo & Tainer, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The data treatment of the scattering data includes normalization of the intensity, background subtraction, and normalization to absolute scale among several steps, which depends on the specific characteristics of the experimental setup. The overall data treatment process and necessary procedure for proper reduction of the scattering data are described in many articles and books in the literature and will not be presented here [7,12,14,15,[23][24][25][26][27][28][29]. In this chapter we will focus on methods for calculation of the SAS intensity, either for oriented or randomly oriented particles.…”
Section: Modeling Methods For Sas Datamentioning
confidence: 99%
“…Several good reviews can be found in the literature for this subject [14,17,36,50,60,65,[67][68][69].…”
Section: Small Angle Scattering and Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular weights were also determined without a standard protein from the SAXS data alone, using the SAXS MoW procedure 65 . The raw data were processed with BioXTAS RAW 66 , and the ATSAS package 67 was used for further analyses and structure modelling. Specifically, distance distribution functions were generated by GNOM 68 , and the programs DAMMIF, GASBOR, BUNCH, and CORAL were used for ab initio and rigid-body modelling 67,69,70 .…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%